Implementing the Pancasila Student Profile to Develop Early Childhood Social Skills - Gisela Silvaina Algazira; Fachrul Rozie; Evie Palenewen; Tri Wahyuningsih (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Prolonged exposure to smartphones has caused many children to become dependent on digital devices as a primary source of entertainment. This condition has been linked to a decline in children's social sensitivity and interaction skills. This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) in enhancing social skills among early childhood learners. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation. The data were analyzed using a thematic approach, and the validity of findings was ensured through data triangulation. The results indicate that the integration of the Pancasila Student Profile in classroom activities has positively influenced the development of children's social skills, particularly in peer interactions. These findings suggest that the P5 initiative can serve as a valuable foundation not only for fostering social skills but also for supporting broader aspects of early childhood development.┬á